Impact of prosthodontic rehabilitation on oral health-related quality of life in the Serbian Armed Forces personnel - Jelić, Nenad; Dragović, Miroslav; Vulović, Stefan; Ristić, Ljubiša; Eraković, Mile; Milosavljević, Marko; Lemić, Tatjana; Milić Lemić, Aleksandra (Vojnosanitetski pregled, 2026)
Background/Aim. Although prosthodontic rehabilitation restores the structural integrity of the stomatognathic system, its impact on patients’ oral health–related quality of life (OHRQoL) remains insufficiently explored, particularly within the military population. The aim of this study was to evaluate the association between the type of prosthetic rehabilitation and OHRQoL, with a specific focus on functional, esthetic, and psychosocial dimensions, as well as to investigate the relationship between these findings and objective oral health indicators. Methods. A cross-sectional study was conducted to assess patient-reported outcomes using the Oral Health Impact Profile-14 (OHIP-14) questionnaire. The study included active duty personnel of the Serbian Armed Forces with natural dentition, as well as personnel with fixed or removable prostheses. Dental status was evaluated through comprehensive clinical examinations conducted by two experienced examiners. Biological parameters included the Caries Activity Factor (CAF) index, the Community Periodontal Index of Treatment Needs (CPITN), the plaque index (PI), and the gingival index (GI). Chronic systemic disease was recorded and included as a covariate in the analyses. Nonparametric statistical tests and multivariable regression analyses were employed to identify independent predictors of OHRQoL. Results. Participants with prostheses reported significantly higher OHIP-14 scores than those with natural dentition (p < 0.0001). No significant differences were observed between fixed and removable prostheses in overall OHIP-14 scores, except within the functional limitation domain, in which fixed prostheses demonstrated a measurable advantage. Multivariable analysis identified oral status, CAF and CPITN indices, and the presence of chronic systemic diseases as independent predictors of OHRQoL, whereas PI, GI, and age were not statistically significant after adjustment. Conclusion. According to the results of this study, prosthetic rehabilitation is associated with improved functional outcomes, but it did not fully alleviate the psychosocial burden associated with tooth loss. The severity of biological oral diseases and general health status were significant predictors of OHRQoL, suggesting that these factors may influence overall quality of life.
Keywords: dental prosthesis; military personnel; oral health; quality of life; serbia; surveys and questionnaires.